Pengaruh Metode Pendidikan al-Quran Orang Dewasa terhadap Kemampuan Membaca al-Quran - Hafsari Hafsari Hafsari (Institut Agama Islam Negeri Palopo, 2018)
This study aims to determine the method of adult Al-Qur'an education (Dirosa) on the ability to read the Koran. This research is descriptive quantitative research with the ex-post facto design. Determination of the sample is 50% of the population entitled 90, namely 45 research samples. The research data use questionnaire and test instruments that have been tested for validity and reliability. Before carrying out data analysis, the data were tested first, namely normality test and homogeneity test. Data analysis The results of the study used descriptive statistical analysis and hypothesis analysis. The results showed that: (1) the method of adult Al-Quran education (Dirosa) as a whole respondents who answered always (SL) by 65%, who answered frequently (SR) by 30%, who answered sometimes (KD) for 5%, who answer rarely (JR) and never (TP) by 0%; (2) Ability to read al-Qur'an respondents with excellent predicate of 43 or 96%, good predicate of 2 or 4%, predicate sufficient, predicate less and predicate failed at 0 or 0%; (3) Based on the results of a simple linear regression analysis to determine the effect of adult Al-Qur'an education methods (variable X) on the ability to read the Qur'an (Variable Y) with the independent variable (method Dirosa) to the honest variable ( Qur'anic reading ability is 67.2%, while other variable costs. Significance value is 0,000 <0,05 so H0 is rejected and H1 is accepted, which means there is a significant (significant) influence of the Dirosa (X) method variable on the ability to read the Qur'an (Y). The interpretation of the r-value of 0.820 shows very strong